COURSE REVIEW OF ENVIRONMENTAL LAW - TATOU EMMANUEL, KOYEU; GRACE MENDI, ANJAH; FRANCOIS XAVIER, TCHAMAGO; VALCIN, FRANKLIN; COLLAZO, LINDA (IJRDO - Journal of Social Science and Humanities Research, 2016)
The right of the environment is a well -built expression of a new politics put in place from 1960 S. It is all about the realization of the limited aspects of natural resources as well as negative effects of pollution of all sorts resulting from the production of goods and their consumption. That specific right derived more or less directly from international debates on the environment, during some important world conferences, has been the object of a transposition in the national elections of States, notably through the constitutionality and the adoption of both legislative and statutory acts, on a threefold plan of supervision, of protection and sanctions.